miR-146a participates in the regulation of cancer stemness of oral carcinoma cells - Yen-Tze Liu; Cheng-Chia Yu; Ming-Yi Lu; Shih-Chi Chao; Yi-Wen Liao; Chuan-Hang Yu; Yu-Hsien Lee (Elsevier, 2023)
Background/purpose: Increasing evidence regarded the existence of cancer stem cells (CSCs) as a leading cause of therapy failure and tumor relapse due to their self-renewal and differentiation abilities. Although ectopic overexpression of micro-RNAs (miRNAs) can modulate the cancer stemness and tumor development in oral cancer, their molecular mechanism is still unclear. Therefore, in the present study, we attempt to uncover the role of miR-146a in the maintenance of oral CSCs. Materials and methods: The expression of miR-146a was determined using qRT-PCR analysis. Aldehyde dehydrogenase (ALDH) enzymic activity and sphere formation assays were used to evaluate the cancer stemness and self-renewal, respectively. Functional assays, including migration/invasion Transwell and colony formation assay, were used to evaluate the aggressive abilities. Luciferase reporter assay was performed to validate the relationship between miR-146a and Numb. Results: In the present study, we reported an increased expression of miR-146a in the oral squamous cell carcinoma (OSCC) specimen, primary OSCC cells sphere, and high ALDH1 activity population within OSCC cells. Inhibition of miR-146a significantly suppressed the ALDH1 activity, self-renewal capacity, and aggressive abilities, including migration, invasion, and colony formation. Moreover, we demonstrated that Numb is a functional target of miR-146a in OSCC-CSCs. Notably, silencing of Numb could retrieve the self-renewal and migration impaired by knockdown of miR-146a. Conclusion: Our results indicate that miR-146a can regulate the cancer stemness in OSCC by modulating Numb, and hence miR-146a/Numb axis can serve as a potential target for oral cancer therapy.